Induction of Therapeutic Protection in an HPV16-Associated Mouse Tumor Model Through Targeting the Human Papillomavirus-16 E5 Protein to Dendritic Cells - Badillo-Godinez, Oscar; Pedroza-Saavedra, Adolfo; Valverde-Garduño, Veronica; Bermudez-Morales, Victor; Maldonado-Gama, Minerva; Leon-Letelier, Ricardo; Bonifaz, Laura C.; Esquivel-Guadarrama, Fernando; Gutierrez-Xicotencatl, Lourdes (Frontiers in Immunology, 2021)
HPV E5 is an oncoprotein mainly expressed in premalignant lesions, which makes it an important target for a vaccine to prevent or cure cervical cancer (CC). In this study, we evaluated whether E5 targeted to DEC-205, present in dendritic cells (DCs), could induce a therapeutic protection against HPV16-induced tumor cells in a mouse model. The HPV-16 E5 (16E5) protein was cross-linked to a monoclonal antibody (mAb) specific to mouse DEC-205 (anti-DEC-205:16E5) or to an isotype control mAb (isotype:16E5). Rotavirus VP6 was cross-linked to the mouse anti-DEC-205 mAb (anti-DEC-205:VP6) as a non-specific antigen control. BALB/c mice were inoculated subcutaneously (s.c.) with the 16E5-expressing BMK-16/myc tumor cells, and 7 and 14 days later the mice were immunized s.c. with the conjugates, free 16E5 or PBS in the presence of adjuvant. Tumor growth was monitored to evaluate protection. A strong protective immune response against the tumor cells was induced when the mice were inoculated with the anti-DEC-205:16E5 conjugate, since 70% of the mice controlled the tumor growth and survived, whereas the remaining 30% developed tumors and died by day 72. In contrast, 100% of the mice in the control groups died by day 30. The anti-DEC-205:16E5 conjugate was found to induce 16E5-specific memory T-cells, with a Th1/Th17 profile. Both CD4+ and CD8+ T cells contributed to the observed protection. Finally, treating mice that had developed tumors with an anti-PD-1 mAb, delayed the tumor growth for more than 20 days. These results show that targeting 16E5 to DEC-205, alone or combined with an immune checkpoint blockade, could be a promising protocol for the treatment of the early stages of HPV-associated cancer.